2010
DOI: 10.3758/s13421-010-0049-9
|View full text |Cite
|
Sign up to set email alerts
|

Orientation priming of grasping decision for drawings of objects and blocks, and words

Abstract: This study tested the influence of orientation priming on grasping decisions. Two groups of 20 healthy participants had to select a preferred grasping orientation (horizontal, vertical) based on drawings of everyday objects, geometric blocks or object names. Three priming conditions were used: congruent, incongruent and neutral. The facilitating effects of priming were observed in the grasping decision task for drawings of objects and blocks but not object names. The visual information about congruent orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Further, because objects and observers can move relative to one another, and therefore motor coding of a grasp movement could change significantly from one moment to the next, it may be inefficient for the motor system to store positional information for more than a few milliseconds before executing an action (Goodale et al 1994). Although previous studies have found no direct influence of varying ISIs (<1 s) on the magnitude of form priming effects for pictures or words (e.g., Carr et al 1982), it is the case that most have used shorter ISIs than 3-4 s as used here (Bub and Masson 2006;Helbig et al 2006;Yoon and Humphreys 2007;Chainay et al 2011;Kiefer et al 2011;Masson et al 2011;Makris et al 2013;Myachykov et al 2013). However, working with real objects in the laboratory presents unique challenges, particularly in terms of controlling tightly stimulus presentation and timing parameters.…”
Section: Tool Action Priming Is Modulated By Taskmentioning
confidence: 93%
See 1 more Smart Citation
“…Further, because objects and observers can move relative to one another, and therefore motor coding of a grasp movement could change significantly from one moment to the next, it may be inefficient for the motor system to store positional information for more than a few milliseconds before executing an action (Goodale et al 1994). Although previous studies have found no direct influence of varying ISIs (<1 s) on the magnitude of form priming effects for pictures or words (e.g., Carr et al 1982), it is the case that most have used shorter ISIs than 3-4 s as used here (Bub and Masson 2006;Helbig et al 2006;Yoon and Humphreys 2007;Chainay et al 2011;Kiefer et al 2011;Masson et al 2011;Makris et al 2013;Myachykov et al 2013). However, working with real objects in the laboratory presents unique challenges, particularly in terms of controlling tightly stimulus presentation and timing parameters.…”
Section: Tool Action Priming Is Modulated By Taskmentioning
confidence: 93%
“…Previous studies have reported robust priming effects from tool stimuli displayed in a range of formats, including not only realistic color photographs (Tucker and Ellis 2001;Grèzes et al 2003;Adamo and Ferber 2009;Makris et al 2011Makris et al , 2013Myachykov et al 2013;Wilf et al 2013;Randerath et al 2013), but also black and white images (James et al 2002;Tucker and Ellis 2004;Bub and Masson 2006;Helbig et al 2006;Yoon and Humphreys 2007;Bub et al 2008;Masson et al 2011), line drawings (Chainay andHumphreys 2002;Handy et al 2003;Chainay et al 2011), and even words (Glover et al 2004;Bub et al 2008;Kiefer et al 2011) which do not inherently convey visual shape cues about object identity. In effect, therefore, it has already been established that priming effects are driven by the identity of an object, and that it is 'safe' to use pictures (including normed pictures from existing databases) as stimuli to investigate priming effects.…”
Section: Tool Action Priming Is Not Modulated By Prime Tangibilitymentioning
confidence: 99%